HUBUNGAN LARI 60 METER DENGAN KEMAMPUAN LOMPAT JAUH SISWA KELAS VIII SMPN 3 TEBING TINGGI - Saputra, Eka; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, this type of research is correlational is a peneltiian to determine the degree of correlation between the different variables. Population in this research is class VIII SMP Negeri 3 Tebing Tinggi, which amounted to 18 people. Selection of samples using total sampling technique thus the sample in this research is class VIII SMP Negeri 3 Tebing Tinggi is 18 people. Analysis of data using correlation and regression analysis. Before testing the hypothesis to test hypotheses and analysis requirements for linearity test regression line by F test using significance level of 5%. Obtained Fhitung = 0.83> Ftabel = 4:41, and the regression equation is Y = 16.75 + 0.83x. Furthermore, to examine the mean correlation between variables X and Y then tested the significance of significance by using the formula t test. From the results of the calculation are known with a value of 0572 while the count r t = 2.79, while table = 1,746. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that